Investment Analysis of Willingness to Pay as Development Effort of The Hot Spring Tourism “Cipanas” of Subang Village, Subang Sub-District, Kuningan Regency, West Java Province - Willfridus Demetrius Siga; Yusuf Siswantara (PINISI Discretion Review, 2021)
The management of natural resources in terms of ecological, social and economic functions and maintaining the aesthetic value of an object and the environment by encouraging the quality of the environment and the sustainability of rural life can be a value of pride and identity of a village. “Cipanas” Hot Spring Tourism Object in Subang Village, Subang District, Kuningan Regency is managed by the local Village Business Entity (BUMDes). This tourism destination is one of the village development efforts for the common welfare (bonnum commune) both economically, socially and sustainably, it needs good governance and capital / investment support. This study aims to analyze the investment of visitors or service users of hot springs in the form of willingness to pay using the Contingent Valuation Method (CVM) to estimate the costs to be incurred by visitors, and multiple regression methods are used to analyze these factors. what factors influence the visitor's willingness to pay. This type of research uses descriptive analysis with a quantitative approach. The results showed that: 1) female consumers, middle-aged, have a Bachelor's or Diploma's latest education, have an employee status, and high income have the highest willingness to pay in a price range that is more than the WTP value, 2) Consumers are willing to pay above the price offered because it has the belief that the hot spring tourism area provides many benefits, 3) The average WTP value is greater than the average market price. This shows that there is an excess price that consumers are willing to pay. 4) The factors that significantly influence the willingness to pay for Cipanas hot water tourism are gender and monthly income. In addition, 52% of respondents are willing to pay for the development of a tourist attraction for the hot spring "Cipanas" in Subang Village.